Serratus anterior plane block reduces perioperative sedation use and discharge analgesia in subcutaneous implantable defibrillator implantation. (24th May 2021) - Mistry, A; Poornanachandran, V; Dhutia, H; Chelliah, R; Pathmanathan, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The subcutaneous implantable cardioverter defibrillator (S-ICD) has now become a well-recognised alternative to traditional devices and can be used as a first-line option, avoiding the risks associated with a transvenous lead. Standard implantation is either performed under general anaesthesia or under sedation. Ultrasound-guided serratus anterior plane block (SAPB) has recently been introduced to provide periprocedural anaesthesia and analgesia. Purpose: To assess whether SAPB reduces periprocedural analgesia/anaesthesia and post-operative analgesia in S-ICD implantation compared with standard perioperative analgesia/anaesthesia. Methods: One hundred and twenty patients eligible for ICD implantation for standard indications were offered a S-ICD over a five-year period (2014-2019) at a single tertiary cardiac centre. From July 2014 to September 2018, consecutive cases were performed with standard analgesia/anaesthesia and performed using a standard two-incision technique. From October 2018 onwards, SAPB was performed in addition to standard perioperative analgesia/anaesthesia. This involved ultrasound-guided infiltration of 50ml prilocaine into the interfascial plane between the serratus anterior muscle and latissimus dorsi at the mid axillary line over the level of the 5th rib. Collection of data was performed at the six-week follow up with all data obtained from routinely collected local registry. Results: The mean age at implant was 52.0 years (+15.9 years) and 102 (85.0%) were male. The mean body mass index was 27.9 (+5.2). 85 (70.8%) had a primary prevention indication. 64 (52.3%) patients had a left ventricular ejection fraction (LVEF) of <35%. 79 (65.8%) patients underwent standard implantation without SAPB (SAPB-) and 41 (34.2%) patients with SAPB (SAPB+). There were no significant differences in age, sex, BMI, left ventricular ejection fraction, comorbidities, aetiology and indication between SAPB- and SAPB+ cohorts. In the SAPB+ cohort, a greater proportion were performed using conscious sedation (97.5% vs 84.8%; p = 0.036) with a lower required dose of midazolam (3.3mg vs 6.4mg; p < 0.001). 34 (83%) patients in the SABP+ cohort required no analgesia at discharge compared for 42 (53.2%) in the SAPB- cohort (p = 0.042). There was a trend towards lesser use of periprocedural morphine (6.2mg vs 7.4mg; p = 0.071) and reduced hospital stay (0.7 days vs 1.1 days; p = 0.102) in the SAPB+ cohort. The use of SAPB did not significantly increase total procedural time (63mins vs 57mins; p = 0.110), defined as the total duration for SAPB administration and S-ICD implantation. There were no periprocedural complications and no complications at follow up. Conclusion: The use of SAPB significantly reduces the dose of sedation required for S-ICD implantation as well as the need for analgesia at discharge without a significant impact on procedure duration.